Brain state-dependent recruitment of high-frequency oscillations in the human hippocampus. (September 2017) - Billeke, Pablo; Ossandon, Tomas; Stockle, Marcelo; Perrone-Bertolotti, Marcela; Kahane, Philippe; Lachaux, Jean-Philippe; Fuentealba, Pablo
Abstract: Ripples are high-frequency bouts of coordinated hippocampal activity believed to be crucial for information transfer and memory formation. We used intracortical macroelectrodes to record neural activity in the human hippocampus of awake subjects undergoing surgical treatment for refractory epilepsy and distinguished two populations of ripple episodes based on their frequency spectrum. The phase-coupling of one population, slow ripples (90–110 Hz), to cortical delta oscillations was differentially modulated by cognitive task; whereas the second population, fast ripples (130–170 Hz), was not seemingly correlated to local neural activity. Furthermore, as cognitive tasks changed, the ongoing coordination of neural activity associated to slow ripples progressively augmented along the parahippocampal axis. Thus, during resting states, slow ripples were coordinated in restricted hippocampal territories; whereas during active states, such as attentionally-demanding tasks, high frequency activity emerged across the hippocampus and parahippocampal cortex, that was synchronized with slow ripples, consistent with ripples supporting information transfer and coupling anatomically distant regions. Hence, our results provide further evidence of neural diversity in hippocampal high-frequency oscillations and their association to cognitive processing in humans.